Penerapan Metode Credit Risk+ Dalam Pengukuran Risiko Kredit Produk Baru: Kredit Wirausaha - , Daniel Tumpal Nico, Se.,Ak. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Increasingly competition in global market including banking industry drives management to change rapidly their business strategy in order to adapt with market condition, one of the result is to bring out the new loan products. This new products need a risk measurement model which can give enough information for management to evaluate all the loan product delivered, especially those product which the working process are being simplified. Credit Risk+ method is one of internal method in credit risk measurement. This method is considered as the suitable method to measure ABC Bankâs new product risk : Kredit Wirausaha. The characteristic of the product which is delivered to small médium enterprises market segmentation, result on various amount of exposures (usually categorized as small amount loan) on large amount of costumers. With great expectation on the result of this study, is to give benefit to ABC Bank management such as a worthful information on new productâs risk and the amount of reserved capital to provide as the consequences of this new product released.